Respuesta :
Given:
f(x) = (x - 5)/8
g(x) = 8x + 5
Therefore
[tex]g(f(x))\\=8( \frac{x-5}{8})+5\\=x-5+5\\=x [/tex]
This means that g(x) is the inverse of f(x) and vice versa.
Answer: g(f(x)) = x
f(x) = (x - 5)/8
g(x) = 8x + 5
Therefore
[tex]g(f(x))\\=8( \frac{x-5}{8})+5\\=x-5+5\\=x [/tex]
This means that g(x) is the inverse of f(x) and vice versa.
Answer: g(f(x)) = x
Answer:
g(f(x))=x.
Step-by-step explanation:
Given :f(x)=[tex]\frac{x-5}{8}[/tex] and g(x)=8x+5.
g(f(x)) = g([tex]\frac{x-5}{8}[/tex]) (Substituting f(x) value)
=[tex]8(\frac{x-5)}{8} +5[/tex] (Replacing x by [tex]\frac{x-5}{8}[/tex])
=x-5+5 (Simplifying)
=x.
g(f(x))=x.